Budaya Organisasi dan Lingkungan Kerja Terhadap Produktivitas Pegawai - Azis, Resky Quinsa Dwi; Beddu, Megawati; Alimuddin, Firman; Lukman, Siti Diva Syarifah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This study aims to determine and express the relationship that exists in the variables of organizational culture and work environment on employee productivity at the Sidenreng Rappang Ministry of Religion Office, both partially and simultaneously. The analysis method used in this research is Multiple Linear Regression Analysis, Validity Test, Rehability Test, Partial Test (t test), Simultaneous Test (F test) and Coefficient of Determination Test (R2 Test) with a total sample respondents of 41 people. The results showed that organizational culture (X1) has a positive and significant effect partially on work productivity (Y) of employees of the Sidenreng Rappang Ministry of Religion Office, with a t-count value of 5.844> t-table 2.024 and a significant value of 0.000 <0.05. Work Environment (X2) has a positive and significant effect partially on work productivity (Y) of employees of the Sidenreng Rappang Ministry of Religious Affairs Office, with a t-count value of 2.588> t-table 2.024 and a significant value of 0.014 <0.05. Each variable simultaneously has a positive and significant effect on the productivity of employees of the Sidenreng Rappang Ministry of Religious Affairs Office with an F-count value of 45.695> F-table 3.24 and a significant value of 0.000 <0.05.